APPLICATION PROGRAM DESIGN WITH TURBO PASCAL PROGRAMMING LANGUAGE FOR MULTIPLE LINEAR REGRESSION EQUATION - Rasiti Rasiti; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2003)
After completing the calculations using manual calculations and computer programs,it can be concluded more effectively use a computerized program. This is caused byusing a computerized time used more quickly.